UJI AKTIVITAS IMUNOMODULATOR FERMENTASI TEH ROSELA JAMUR KOMBUCHA TERHADAP PROLIFERASI SEL LIMFOSIT MENCIT GALUR BALB/C SECARA IN VITRO - Maria Ulfah; Dinar Putri Octaviani; Ediati Sasmito (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Recently, some research showed that there is an immunomodulator effect in the fermentation of Rosella kombucha mushroom  tea and it can be caused by flavonoid and organic acid. The purpose of this research was to show the activity of immunomodulator Rosella kombucha mushroom  tea to against the proliferation of lymphocyte cells of Balb/C mice in vitro and to show the dose and length of fermentation that induces highest immunomodulator activity.  Kombucha mushroom was fermented for 5 days, 10 days and also 15 days with boiled Rosella tea, water and sugar. The yield of fermentation in the concentration of 6,25; 12,5; 25; 50 and 100 µg/mL were tested on lymphocyte cells proliferation by the MTT Assay. The OD (Optical Density) data obtained was  statistically analyzed by nonparametric Friedman test and continuoused by Mann-Whitney test. The result of this research showed that the fermentation of Rosella kombucha mushroom tea  has an immunostimulatory activity on lymphocyte cells proliferation with the concentration 6,25; 12,5 and 25 µg/mL in the 10 days and the highest immunostimulatory activity  showed by the concentration 25 µg/mL and 10 days of fermentation time. Key words: immunomodulatory, optical density, Rosella kombucha mushroom tea.